Novels into film - Bluestone, George (Johns Hopkins University Press, 2003)
First published in 1957, this seminal work of film theory analyzes the process - "the mysterious alchemy"- by which novels are transformed into films. Beginning with a discussion of the aesthetic limits of both the novel and the film, George Bluestone goes on to offer close readings of six films based on novels of serious literary merit - The Informer, Wuthering Heights, The Grapes of Wrath, Pride and Prejudice, The Ox-Bow Incident, and Madame Bovary - focusing on the additions, deletions, and other changes made by the filmmakers in adapting the source material for the screen. Based on both in-depth research into film archives and libraries and on interviews with the screenwriters, directors, and producers who worked on these films, Novels into Film concludes that because the novel lends itself to states of consciousness and the film to observed reality, the adaptation of one from the other produces a new and wholly autonomous art form.